Identification of Malay Arabic and Bugis Script in West Kalimantan - Patmawati, Patmawati; Zakirman, Al Fakhri (The Pontianak State Institute of Islamic Studies, 2019)
The spread of Islam in West Kalimantan was carried out by merchants, dai, and sea nomads (pasompe) who came from various kingdoms. At that time scientific reformation, seen from the cultural heritage they left behind in the form of manuscripts that were widely spread among the community. This research is a field research that will study Malay Arabic and Bugis script with a philological approach, because some of these texts use handwriting with Malay Arabic and Bugis scripts. The researcher carried out an inventory of existing texts described and the researchers transliterated Malay Arabic and Bugis characters into latin script and then translated them into Indonesian. In this study, researchers focused on the study of manuscript classification.The results of this study indicate that West Kalimantan has many manuscripts that are stored on script lovers, the general public, students from the scholars of scriptwriters, descendants of script writers and others. There are 24 manuscripts that the researchers succeeded in, 21 manuscripts with Malay Arabic and Malay languages, four of which are translations of Arabic texts. One manuscript is Bugis and Bugis, and one other manuscript is Malay Arabic but Bugis. One manuscript and Arabic.